If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3XY + 5Y = 7 Solving 3XY + 5Y = 7 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5Y' to each side of the equation. 3XY + 5Y + -5Y = 7 + -5Y Combine like terms: 5Y + -5Y = 0 3XY + 0 = 7 + -5Y 3XY = 7 + -5Y Divide each side by '3Y'. X = 2.333333333Y-1 + -1.666666667 Simplifying X = 2.333333333Y-1 + -1.666666667 Reorder the terms: X = -1.666666667 + 2.333333333Y-1
| (x-2)x=3x(2x+1) | | 58=-2(m+4)m | | r^2-19t+18=0 | | r^2-9t+18=0 | | 1000=x(30-2x)(20-2x) | | -30a=-20 | | -30=-20 | | 7x-14=11x | | -2x-4=24 | | -2(2x-6)=20 | | -2(x+5)=30 | | 2(2x-6)=40 | | 4x-2x+2=16 | | x-5x+4=-8 | | 2x+8x=17 | | -7x+5x+2=20 | | x-8-3=10 | | 8z=40 | | 24x-3=15+45x | | 9t=-16t^2+60t | | -13y-7y=-140 | | 2x-7=20+12x | | 13y-7y=-140 | | -10x-3x=-39 | | 3x+4y+z= | | -4x-8x=48 | | 60*0-30x=-180 | | c=a+ab | | 3a(n+7)=43 | | 60y-30x=-180 | | 3p^2+12p+11=0 | | 3(2x-3)=63 |